IMPACT OF ORGANIZATIONAL CULTURE ON KNOWLEDGE SHARING IN INDONESIAN SOFTWARE DEVELOPMENT COMMUNITY - Indra, Muhammad Nadhirsyah; Anditama, Muhammad Rizky; Sensuse, Dana Indra; Lusa, Sofian; Safitri, Nadya; Elisabeth, Damayanti (Jurnal Teknoinfo, 2025)
In the dynamic landscape of software development, effective knowledge sharing is vital for fostering collaboration and innovation among development teams. This study examines the intricate dynamics influencing knowledge sharing among software developers within organizational contexts, focusing on the pivotal factors of organizational culture. Key factors such as communication, trust, leadership, reward systems, and organizational structure are investigated to comprehend their impact on knowledge-sharing behavior. The research model posits hypotheses exploring positive relationships between trust, communication, leadership, organizational structure, reward systems, and knowledge sharing. Data was collected through online surveys completed by 62 software developers in Indonesia, and SmartPLS 3 was used for the analysis. Measurement models were employed to evaluate internal consistency reliability, convergent validity, and discriminant validity, while structural models assessed the explanatory potential. Results indicate that the explanatory power of the model is weak, suggesting a need for further exploration. Leadership and reward systems were found to have a positive influence on knowledge sharing, although the impact of organizational structure remains inconclusive. The study emphasizes the critical roles of reward structures and leadership in encouraging knowledge sharing and presents practical implications for companies aiming to enhance their knowledge management practices. These findings highlight the necessity for organizations to foster leadership and implement effective reward systems to promote a culture of knowledge sharing. Furthermore, the study suggests improvements in assessment techniques and calls for a reevaluation of the connection between organizational structure and knowledge sharing. This research contributes to the understanding of how organizational culture impacts knowledge sharing within the software development community in Indonesia, providing valuable insights for both academic researchers and industry practitioners.